Needlestick and sharps injuries among nurses at Atatürk university research hospital and their practices after injury - Çalıkoğlu, Elif Okşan; Bedir, Banu; Akçay, Hilal Betül; Gümüş, Ali (The European Research Journal, 2019)
Objectives: Exposure to needlestick and sharps injuries (NSI) is among the major occupational risks of health workers. Yearly 385,000 NSI are reported by health workers. In this study, we aimed to evaluate the frequency of NSI among nurses at Atatürk University Research Hospital together with the elaboration of the utilization of effective preventive measures used for infection control as well as the affecting factors. Methods: All 562 nurses working at Atatürk University Research Hospital during September-November 2016 were invited to fill a questionnaire with 27 items. Questions were asked about the sociodemographic characteristics,having experienced NSI, usage of protective equipment, and hepatitis B vaccination status. A total of 555 (98.7%) nurses volunteered to participate. Verbal consent was taken from the participants. Results: Of the participants, 425 (76.6%) were females, and 130 (23.4%) were males. Their mean age was 27.5 ± 7.4 years. 52.6% (n = 293) of the participants were in the surgical clinics while 47.4% (n = 262) were in the medical clinics. Of the participants, 21.6% (n = 120) stated that they experienced a needlestick or sharps injury within the last one year. Of those injuries, 16.7% (n = 20) happened while removing the needle tip from the syringe, 29.2% (n = 35) while trying to reattach the needle cap, 16.7% (n = 20) while filling the syringe, and 12.5% (n = 15) while drawing blood from the patient. Conclusion: Health workers should be trained on injuries and all other occupational risks with cutting and puncturing tools, and they should be instructed on the use of protective equipment.